Seronoknya solat / Zawani Badri … [et al.] - Badri, Zawani; Ismail, Shahiszan; Ismail, Nor Azira; Laidin, Jamilah; Ismail, Marhapizah (Division of Research and Industry Linkages, 2017)
Autism spectrum disorders (ASDs) can be categorized as developmental disabilities that can be diagnosed as early as three years old and affected a child for a lifetime. Mostly, children with ASD find social interaction and communication are challenging for them as they process information differently than normal children. However, children with ASD do not necessarily face the same challenges. Nevertheless, with appropriate and intensive educational approaches, children with ASD can still live a normal life like others. Therefore, "Seronoknya Solat” is initiated in order to assist ASD children to learn the practical part of daily prayer which are the movement, body positions and the sequence of five daily prayers and performing ablution (wudu1). The idea of this book is derived from several approaches that commonly practiced for children with ASD namely adapted book and using visual supports for timetable/schedule. Adapted book is one of the approaches that is commonly practised among child disabilities including ASD as the content of the book is adapted from the original book but with motor and visual supports in order to develop literacy among children with ASD. Most of the adapted books available only addressed ASD child's common daily activities but lack of prayer book for Muslim. Since a child with ASD can process visual faster than auditory information, the concept of adapted books kits is utilised in order to introduce five daily prayers to the children with ASDs. Besides, children with ASD can respond well to structure although they may find it difficult to deal with transitions. Therefore, the idea of visual timetable concept is also integrated in developing this book in order to help children with ASD to structure activities involved in performing wudu’ and daily prayers into step that are manageable and clear so that it can be developed into a routine in future, the theory part which is the memorization of prayers should be included in this book.